Iron(ii) complexes of 4-sulfanyl-, 4-sulfinyl- and 4-sulfonyl-2, 6-dipyrazolylpyridine ligands. A subtle interplay between spin-crossover and crystallographic phase changes. Issue 7 (17th June 2015) - Kershaw Cook, Laurence J.; Kulmaczewski, Rafal; Barrett, Simon A.; Halcrow, Malcolm A.
Abstract : The compound shown exhibits an abrupt thermal spin-transition, with an accompanying crystallographic phase change at slightly lower temperature which is visible as a shoulder on the susceptibility curve. Abstract : Oxidation of 4-(methylsulfanyl)-2, 6-di(pyrazol-1-yl)pyridine (L SMe ) with hydrogen peroxide or mCPBA yields 4-(methylsulfinyl)-2, 6-di(pyrazol-1-yl)pyridine (L SOMe ) and 4-(methylsulfonyl)-2, 6-di(pyrazol-1-yl)pyridine (L SO2 Me ), respectively. Solid [Fe(L SMe )2 ][ClO4 ]2 (1[ClO4 ]2 ) is high-spin at room temperature, and exhibits an abrupt spin-transition at T 1/2 = 256 K. A shoulder on the cooling side of the χ M T vs . T curve is associated with a hysteretic crystallographic phase change, occurring around T ↓ = 245 K and T ↑ = 258 K. The phase change involves a 180° rotation of around half the methylsulfanyl substituents in the crystal. This contrasts with the previously reported BF4 − salt of the same compound, which is isostructural to1[ClO4 ]2 at room temperature but transforms to a different crystal phase in its low-spin state. Solid [Fe(L SOMe )2 ][BF4 ]2 (2[BF4 ]2 ) and [Fe(L SO2 Me )2 ][BF4 ]2 (3[BF4 ]2 ) both exhibit gradual spin-crossover equilibria centred significantly above room temperature. Solution measurements show that the oxidised sulfur centers in2[BF4 ]2 and3[BF4 ]2 stabilise the low spin states of those complexes.